Effectiveness of Online Group Interventions with Digital Literacy and Internet Ethics E-Modules for Preventing Cyberbullying among Students - Henri Gunawan Risal; Firdayani Syarifuddin; Ibnu Hajar Manippi; Hilda Suci Ramadhani; Jessy Angel Casey Ampulembang; Eva Ulfiani (Jurusan Teknik Informatika dan Komputer, 2024)
This study investigates the effectiveness of online group interventions assisted by e-modules on digital literacy and ethical online behavior to prevent cyberbullying among university students. Cyberbullying remains a pervasive issue in higher education, yet scalable interventions that combine knowledge acquisition and behavioral engagement are limited. This research aims to address this gap by evaluating whether a structured microlearning and chatbot-supported online program can enhance students’ knowledge, ethical awareness, and preventive behavioral intentions. An experimental study with pretest-posttest control group design was conducted involving 80 undergraduate students randomly assigned to intervention (n = 40) and control groups (n = 40). The intervention included interactive e-modules, scenario-based discussions, and AI chatbot support over a three-week period. Data were collected on digital literacy, ethical awareness, and behavioral intentions using validated Likert-scale instruments. Statistical analysis was performed using paired t-tests, independent t-tests, and effect size calculations to evaluate intervention outcomes. The intervention group demonstrated significant improvement compared to the control group in digital literacy (mean increase 30.2 points, Cohen’s d = 2.31), ethical awareness (mean increase 1.23, d = 2.10), and behavioral intention to prevent cyberbullying (mean increase 1.30, d = 2.18). Usability scores were high (SUS = 84.2 ± 6.3), and engagement metrics correlated positively with learning outcomes (r = 0.62, p < 0.001). The study demonstrates the potential of scalable online group interventions to enhance preventive digital behavior in higher education. Limitations include a single-institution sample, short intervention duration, and reliance on self-reported behavioral intentions. Future research should examine long-term effects, multi-institutional samples, and objective behavioral measurements. This research provides empirical evidence supporting the integration of e-modules, interactive group sessions, and chatbot support for cyberbullying prevention, contributing to digital citizenship education. The framework offers a practical, scalable, and adaptable model for universities seeking to promote safe and ethical online behavior.